Genetic resistance to gastro-intestinal nematode parasites in Galla and Small East African goats in the sub-humid tropics - Baker, R.L.; Audho, James O.; Aduda, Eric O.; Thorpe, W.R. (2001)
A study was carried out from 1992 to 1996 to compare the resistance to naturally acquired gastro intestinal (GI) nematode parasite infections (predominantly Haemonchus contortus) of Galla and Small East African goats in the sub humid coastal region of Kenya. A total of 204 Galla and 349 Small East African (SEA) kids were born from five kiddings. These were the progeny of 18 Galla and 17 SEA bucks. Live weights (LWT), blood packed cell volume (PCV) and faecal egg count (FEC) were recorded at 1 to 2 month intervals from birth to about 14 months of age. The SEA kids were more resistant to GI nematode parasites than Galla kids as shown by their significantly lower FEC (P < 0.001) in the post weaning period (8 to 14 month old kids) and lower mortality from birth to 14 months of age (P < 0.05). There was no significant (P > 0.05) breed effect on PCV, but Galla kids were significantly heavier (P < 0.001) at all measurement times between birth and 14 months of age. Heritability estimates for LWT, PCV and FEC at the different sampling times were characterized by high standard errors. Heritability estimates for records taken at 4.5 and 8 months of age from a repeated measures analysis were 0.18 (s.e. 0.08) for PCV and 0.13 (s.e. 0.07) for logarithm transformed FEC. The phenotypic and genetic correlation estimates between PCV and LFEC were moderately to highly negative and averaged 0 36 and 0 53, respectively. The results are discussed in relation to the limited evidence for resistance to GI nematode infections in goats and compared with the much stronger evidence for resistance in sheep.